2018
DOI: 10.1101/314583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reversible two-state folding of the ultrafast protein gpW under mechanical force

Abstract: Ultrafast folding proteins have limited cooperativity and thus are excellent models to resolve, via single-molecule experiments, the fleeting molecular events that proteins undergo during folding. Here we report single-molecule atomic force microscopy (AFM) experiments on gpW, a protein that, in bulk, folds in a few microseconds over a marginal folding barrier (~1 kBT). Applying pulling forces of only 5 pN we maintain gpW in quasiequilibrium near its mechanical unfolding midpoint, and detect how it interconver… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…From the interpretation of the equilibrium and kinetic data, gpW was shown to have a small barrier (~1 k B T ) at the thermal denaturation midpoint and to fold downhill in native conditions 16 . In our constant force experiments in the low force regime, we found that gpW behaved like a two-state folder, with a binary switching pattern indicative of a force-induced free energy barrier 13 (Fig. 1B), as confirmed by molecular simulations using a coarse-grained model.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…From the interpretation of the equilibrium and kinetic data, gpW was shown to have a small barrier (~1 k B T ) at the thermal denaturation midpoint and to fold downhill in native conditions 16 . In our constant force experiments in the low force regime, we found that gpW behaved like a two-state folder, with a binary switching pattern indicative of a force-induced free energy barrier 13 (Fig. 1B), as confirmed by molecular simulations using a coarse-grained model.…”
Section: Introductionsupporting
confidence: 68%
“…The data shows a distinct two-state like hopping pattern between the high (unfolded) and low extension (folded) states in the measured extension ( q ) vs time plots. In our previous work we described how this binary switching pattern, unexpected for an ultrafast downhill folder, is indicative of a force-induced barrier 13 . This was observed experimentally by us for the first time after predictions from simulations of nucleic acids by Hyeon and Thirumalai 17 and, in the context of protein folding, by Fernández and his co-workers 18 .…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…No other single-molecule technique can reach the upper force ranges of AFM and explore ultra-stable folds and interactions. Unfortunately, although some successful examples exist 19,20 , its decreased resolution at low force ranges and instability have prevented the identification of protein folding events and slow-kinetic molecular events that occur at forces below 20 pN and in narrow ranges. By contrast, magnetic tweezers, since its first implementation for protein studies 21 , has demonstrated that its sub-pN resolution and week-long stability in the 0.1-120 pN range outcompete AFM for exploring protein dynamics at low forces and for extended periods [22][23][24][25][26] (Fig.…”
Section: Introductionmentioning
confidence: 99%